1993
DOI: 10.1152/jappl.1993.74.1.170
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of coactive muscles during fatigue

Abstract: Coactivation is antagonist muscle activity that occurs during voluntary contraction. Recently, we showed that the extent of coactivity in the knee flexors decreases after a short period of resistance training of the knee extensors (8). The purpose of the present experiment was to study the time course of coactivation in the knee flexors during fatigue of the knee extensors. Ten male subjects performed repeated submaximal static leg extensions in a low-intensity long-duration and a high-intensity short-duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
96
2
12

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 11 publications
26
96
2
12
Order By: Relevance
“…As pointed out by several investigators (Jahnke et al 1989;Proske et al 1993;Nordin & Hagbarth, 1996) the after-effects of a conditioning isometric voluntary contraction are highly dependent on the unconditioned state of the muscle, in which the stiffness or slackness of both extra-and intrafusal muscle fibres at any given time may vary as a result of thixotropic after-effects which remain after preceding movements andÏor contractions. It has previously been demonstrated that antagonistic muscles are co-activated during forceful voluntary isometric contractions of a given muscle group (Psek & Cafarelli, 1993). Thus, it is probable that in the present experiments the forceful hold-short arm abductor contractions were also accompanied by contractions in the arm adductors for which the conditioning contractions were of the 'hold-long' type.…”
Section: Discussionmentioning
confidence: 54%
“…As pointed out by several investigators (Jahnke et al 1989;Proske et al 1993;Nordin & Hagbarth, 1996) the after-effects of a conditioning isometric voluntary contraction are highly dependent on the unconditioned state of the muscle, in which the stiffness or slackness of both extra-and intrafusal muscle fibres at any given time may vary as a result of thixotropic after-effects which remain after preceding movements andÏor contractions. It has previously been demonstrated that antagonistic muscles are co-activated during forceful voluntary isometric contractions of a given muscle group (Psek & Cafarelli, 1993). Thus, it is probable that in the present experiments the forceful hold-short arm abductor contractions were also accompanied by contractions in the arm adductors for which the conditioning contractions were of the 'hold-long' type.…”
Section: Discussionmentioning
confidence: 54%
“…Indeed, several studies have shown that the force generating capacity of the antagonist muscles remained equal after fatiguing contractions of the agonist muscles (e.g., Levenez et al 2005). Although the eVects on the EMG amplitude and median frequency of the antagonist muscle could, in principle, result from cross-talk, it is typically interpreted as an eVect of a common drive to the agonist-antagonist couple (Psek and Cafarelli 1993;Ebenbichler et al 1998;Mullany et al 2002;Levenez et al 2005). In support of this interpretation, an increase in amplitude and a decrease in median frequency have been found in the contralateral homologous muscle after unilateral muscle fatigue (Morrison et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Outra possível relação que poderia ser realizada como forma de compreensão dos resultados obtidos trata-se da coativação (Weir et al, 1998;. Psek;Cafarelli;, a qual consiste na atividade do músculo antagonista durante contração voluntária.…”
Section: Discussionunclassified
“…Psek;Cafarelli;, a qual consiste na atividade do músculo antagonista durante contração voluntária. A coativação muscular dos flexores do joelho durante fadiga de seus extensores demonstra que um aumento da força dos isquiotibiais pode diminuir a força produzida pelo quadríceps (WEIR et al, 1998).…”
Section: Discussionunclassified
See 1 more Smart Citation